Pengaruh Pembiayaan Murabahah Dan Musharakah Terhadap Profitabilitas Di Bprs Madinah Lamongan Periode 2014-2017 - Wahyuni Wahyuni (JES (Jurnal Ekonomi Syariah), 2019)
Financial report is data which can provide an illustration and information. The information that is given is a description of enterprise at some point or another certain or at a particular period. Financial report is an analysis used to know the meaning of set forth in the number that such financial statement so that beneficial for the users. In addition, by analyzing the influence of an financial report can be seen divorce or funding murabahah and musharakah in effecting company profitability. This research attempts to answer the question of how the influence of murabahah financing to profitability in BPRS Madinah Lamongan, how the influence of musharakah financing to profitability in BPRS Madinah Lamongan, and how the influence of murabahah financing and musharakah simultaneously on the profitability in BPRS Madinah Lamongan. This research is quantitative model which describes the phenomena of objects research and take conclusions  based on figures the statistical analysis. Data collection is carried out by interviews from employees of BPRS Madinah Lamongan and documentation with the methods for data collection of financial report BPRS Madinah Lamongan 2014-2017 Period. The results of research shows that first, murabahah financing has an influence on the profitability in BPRS Madinah Lamongan 2014-2017 period. It is otherwise based on the partial test. Second, musha>rakah financing has no influence to profitability in BPRS Madinah Lamongan 2014-2017 period. It is otherwise based on the partial test. And third, murabahah financing and musharakah together fit to influence to profitability in BPRS Madinah Lamongan 2014-2017 period. This is proven with F test that produce  significant values ≥ 0,05. Keywords: Murabahah and Musharakah Financing, Profitability, BPRS Madinah Lamongan